USE OF TECHNOLOGY IN LEARNING BY STUDENTS OF THE FACULTY OF SCIENCE AND TECHNOLOGY - Sahar, Yusman; Darius Tandirerung; Nuraisyah Takdir (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This research aims to analyze the use of technology in learning by students of the Faculty of Science and Technology at Amal Ilmiah Yapis Wamena University. This research was conducted from January to February 2025 using a quantitative approach. Data were collected through surveys of students and observations of the use of various technologies in the learning process. The research results show that the use of technology in learning is still low. There are several obstacles such as limited internet access and a lack of digital skills among some students. To enhance the effectiveness of technology use, strengthening infrastructure, digital literacy training, and optimizing the use of blended learning methods are necessary. Thus, the integration of technology in learning can be more optimal in supporting students' academic processes.